Test pattern [videorecording (DVD)] - Ford, Shatara Michelle; Hall, Brittany S., 1987-; Brill, Will, 1986-; Bean, Gail; Fuller, Drew, 1980- (Kino Lorber, 2021)
The movie follows an interracial couple whose relationship is put to the test after a Black woman is sexually assaulted and her white boyfriend drives her from hospital to hospital in search of a rape kit. Their story reveals the systemic injustices and social conditioning women face when navigating sex and consent within the American patriarchy. Winner of top prizes at the BlackStar and New Orleans Film Festivals, this gripping social thriller offers a unique exploration of institutional racism and sexism from a Black female point of view.